Pemanfaatan Teknologi Informasi Sebagai Media Inovatif Dalam Pendidikan Kewirausahaan di Era Digital: Kajian Systematic Literature Review Menggunakan Metode PRISMA - Sutri, Ridwan; Veri, Jhon (Indo-MathEdu Intellectuals Journal, 2025)
Digital transformation has significantly influenced educational approaches, including entrepreneurship education. This study aims to examine the use of information technology as an innovative medium in entrepreneurship education in the digital era through a Systematic Literature Review (SLR) using the PRISMA method. A total of 100 articles were collected from various academic databases such as Google Scholar, ScienceDirect, and IEEE Xplore, and after screening, 70 relevant articles were selected for analysis. The results show that the integration of information technology—such as e-learning, Learning Management Systems (LMS) aims to identify commonly used data analysis techniques in a systematic literature review (SLR) approach based on the PRISMA method, business simulations, and social media—can enhance students’ learning motivation, creativity, and entrepreneurial skills. Technology also enables more flexible, interactive, and contextual learning. However, several challenges remain, including limited infrastructure and the readiness of educators to adopt technological tools effectively. This study concludes that the utilization of information technology is a crucial strategy for developing adaptive and future-oriented entrepreneurship education.